2021
DOI: 10.1101/2021.02.05.21251182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single mRNA immunization boosts cross-variant neutralizing antibodies elicited by SARS-CoV-2 infection

Abstract: The emergence of SARS-CoV-2 variants raises concerns about their resistance to neutralizing antibodies elicited from previous infection, or from vaccination. Here we examined whether sera and monoclonal antibodies from convalescent donors, prior to and following a single immunization with the Pfizer or Moderna mRNA vaccines, neutralize the Wuhan-Hu-1 strain and a variant, B.1.351 from South Africa. Pre-vaccination sera weakly neutralized Wuhan-Hu-1 and sporadically neutralized B.1.351. Immunization with either… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(46 citation statements)
references
References 94 publications
7
39
0
Order By: Relevance
“…Overall, these data also add to our understanding of SARS-CoV2 mRNA vaccine-induced immune responses in several ways. First, our serological data is consistent with several other recent studies 9,10,12,13,16,17 indicating robust boosting of antibody responses in SARS-CoV2 recovered subjects after the first vaccine dose, but little benefit to antibody titers after the second vaccine dose. Moreover, we identified a similar effect for virus-specific memory B cells, demonstrating that both a quantitative and qualitative plateau in vaccine-induced memory B cells is achieved following the first dose of vaccine with little additional change to the memory B cell response following booster vaccination.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, these data also add to our understanding of SARS-CoV2 mRNA vaccine-induced immune responses in several ways. First, our serological data is consistent with several other recent studies 9,10,12,13,16,17 indicating robust boosting of antibody responses in SARS-CoV2 recovered subjects after the first vaccine dose, but little benefit to antibody titers after the second vaccine dose. Moreover, we identified a similar effect for virus-specific memory B cells, demonstrating that both a quantitative and qualitative plateau in vaccine-induced memory B cells is achieved following the first dose of vaccine with little additional change to the memory B cell response following booster vaccination.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, several recent studies have indicated that antibody responses can be robustly induced in SARS-CoV2 experienced individuals, consistent with an anamnestic response 912 . Although one study suggests that memory B cells might also be boosted after a single vaccine dose 13 , it remains unclear how well memory B cell responses are induced in SARS-CoV2 naïve versus SARS-CoV2 experienced subjects after one versus two doses of mRNA vaccine. Moreover, how antibody levels predict or relate to memory B cell responses following mRNA vaccination remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…We observed no neutralizing activity in plasma from vaccinated SARS-CoV-2 naïve individuals (Figure 3A), in agreement with previous findings 38 . As recently described 22, 57 , we observed that pre-existing SARS-CoV-2 neutralizing antibody responses were significantly boosted by a single dose of Spike-encoded mRNA vaccine (Figure 3A). Interestingly, a single dose enlarged the potency of the neutralizing response that was now able to efficiently neutralize pseudoviral particles bearing the B.1.1.7 Spike or from other variants with different concerning mutations (E484K, S477N, N501Y, N501S) (Figure S2E-G).…”
Section: Resultssupporting
confidence: 84%
“…The E484K mutation, is part of the South African B.1.351 variant and is now found in several SARS-CoV-2 genomes worldwide that spread rapidly 17 . Studies have shown that this mutation increases affinity of the S glycoprotein for ACE-2 18 and confers resistance to neutralization mediated by mAbs and plasma from naturally-infected and vaccinated individuals 19–22 . The S477N mutation confers a higher affinity for the ACE-2 receptor and has rapidly spread to many countries in Oceania and Europe 2328 .…”
Section: Introductionmentioning
confidence: 99%
“…All of these mutations are located in the receptor binding site (RBS) of the receptor binding domain (RBD) of the spike (S) protein (Figure 1A). Two of these three mutations, K417N and E484K, decrease the neutralizing activity of sera as well as of monoclonal antibodies isolated from COVID-19 convalescent plasma and vaccinated individuals ( 410 ). Previous studies have shown that certain IGHV genes are highly enriched in the antibody response to SARS-CoV-2 infection, especially IGHV3-53 ( 1115 ) and IGHV1-2 ( 12, 16, 17 ).…”
Section: Introductionmentioning
confidence: 99%